Given that ray AC bisects angle A, it means that the measure of angle BAC is equal to the measure of angle CAD.
Since it is given that \( m\angle BAD = 46^\circ \), we can express angle BAD as the sum of angles BAC and CAD:
\[ m\angle BAD = m\angle BAC + m\angle CAD \]
Since ray AC bisects angle A, we have:
\[ m\angle BAC = m\angle CAD \]
Let's denote \( m\angle BAC = x \). Then:
\[ m\angle BAD = x + x = 2x \]
Setting it equal to 46 degrees gives us:
\[ 2x = 46^\circ \]
Solving for \( x \):
\[ x = \frac{46^\circ}{2} = 23^\circ \]
Thus, \( m\angle BAC = 23^\circ \).
So the correct response is:
The \( m\angle BAC \) is 23 degrees.